IRE1α Implications in Endoplasmic Reticulum Stress-Mediated Development and Pathogenesis of Autoimmune Diseases - Junjappa, Raghu Patil; Patil, Prakash; Bhattarai, Kashi Raj; Kim, Hyung-Ryong; Chae, Han-Jung (Frontiers in Immunology, 2018)
Inositol-requiring transmembrane kinase/endoribonuclease 1α (IRE1α) is the most prominent and evolutionarily conserved endoplasmic reticulum (ER) membrane protein. This transduces the signal of misfolded protein accumulation in the ER, named as ER stress, to the nucleus as “unfolded protein response (UPR)”. The ER stress-mediated IRE1α signaling pathway arbitrates the yin and yang of cell life. IRE1α has been implicated in several physiological as well as pathological conditions, including immune disorders. Autoimmune diseases are caused by abnormal immune responses that develop due to genetic mutations and several environmental factors, including infections and chemicals. These factors dysregulate the cell immune reactions such as cytokine secretion, antigen presentation, and autoantigen generation. However, the mechanisms involved, in which these factors induce the onset of autoimmune diseases, are remaining unknown. Considering that these environmental factors also induce the UPR, which is expected to have significant role in secretory cells and immune cells. The role of the major UPR molecule, IRE1α, in causing immune responses is well identified, but its role in inducing autoimmunity and the pathogenesis of autoimmune diseases has not been clearly elucidated. Hence, a better understanding of the role of IRE1α and its regulatory mechanisms in causing autoimmune diseases would could help to identify and develop the appropriate therapeutic strategies. In this review, we mainly center the discussion on the molecular mechanisms of IRE1α in the pathophysiology of autoimmune diseases.